Pengaruh Kualitas Pelayanan, Harga Dan Kepercayaan Terhadap Loyalitas Pelanggan Pada Jasa Pengiriman J&T Express Cabang Kedoya Raya 2 - Holifatun Fatonah; Rani Rani; Purwatiningsih Purwatiningsih (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2023)
This study aims to analyze the effect of service quality, price and trust on customer loyalty at J&T Express Kedoya Raya 2 branch. This type of research uses descriptive quantitative. Theauthors in this study are all J&T Express Kedoya Raya Branch Customers 2. Determination of the number of research samples using accidental sampling techniques, namely by multiplying the analyzed indicators by multiplier factors so that as many as 100 samples are obtained. The collected data was analyzed using the SPSS 25 program. The results showed that: (1) service quality did not have a significant effect on customer loyalty at J&T Express Kedoya Raya Branch 2, (2) price did not have a significant effect on customer loyalty at J&T Express Kedoya Raya Branch 2, (3) trust had a significant effect on customer loyalty at J&T Express Kedoya Raya Branch 2, (4 ) s 53.3% of the variables of service quality, price and trust simultaneously have a significant influence on customer loyalty at J&T Express Kedoya Raya Branch 2.